Mineral and Climatic Controls Over Soil Organic Matter Stability Across the Tibetan Alpine Permafrost Region - Fang, Kai; Chen, Leiyi; Qin, Shuqi; Zhang, Qiwen; Liu, Xuning; Chen, Pengdong; Yang, Yuanhe (Global Biogeochemical Cycles, 2021)
Permafrost thaw could accelerate microbial decomposition, lead to greenhouse gases emissions into the atmosphere, and thus trigger a positive feedback to climate warming. As a key parameter reflecting the resistance of soil organic matter (SOM) to be decomposed by microorganisms, SOM stability may determine the strength of permafrost carbon (C)-climate feedback. Adequate understanding of patterns and drivers of SOM stability can thus contribute to predicting permafrost C cycle and its feedback to climate change. However, due to limited observations, it remains unknown whether biochemical selectivity or physico-chemical protection dominates SOM stability in permafrost regions. By combining large-scale soil sampling, thermal analysis and random forest model, we quantified SOM stability in the top 10 cm using thermogravimetry and differential scanning calorimetry, and explored its spatial patterns across the Tibetan alpine permafrost region. We then constructed structural equation model to evaluate the relative importance of climatic variables, edaphic properties, substrate quality, and mineral variables in regulating SOM stability over a broad geographic scale. Our results indicated that SOM stability exhibited an increasing tendency from the southeastern to northwestern plateau. The stronger SOM stability was associated with higher mineral-organic associations and more arid conditions. By contrast, substrate quality had limited effects on SOM stability. Overall, these results provide large-scale evidence for the physico-chemical protection hypothesis, highlighting the importance of considering mineral variables in Earth system models to better predict soil C dynamics across permafrost regions.